ChemInform Abstract: Ultrathin Ca‐PO4‐CO3 Solid Solution Nanowires: A Controllable Synthesis and Full‐Color Emission by Rare‐Earth Doping. Issue 5 (13th February 2013) - Hui, Junfeng; Yu, Qiyu; Long, Yong; Zhang, Zhicheng; Yang, Yong; Wang, Pengpeng; Xu, Biao; Wang, Xun
Abstract Ultrathin Ca‐PO4‐CO3 solid solution nanowires are synthesized from aqueous solutions of Ca(NO3)2, Na2CO3, and Na3PO4 containing octadecylamine, EtOH, and oleic acid (autoclave, 90—220 °C, 12 h).